Women's Experiences of Using Anabolic Androgenic Steroids - Börjesson, Annica; Ekebergh, Margaretha; Dahl, Marja-Liisa; Ekström, Lena; Lehtihet, Mikael; Vicente, Veronica (Frontiers in Sports and Active Living, 2021)
Anabolic androgenic steroids are used by women to increase their muscle mass and because of their performance-enhancing effects. Despite permanent/high risk of side effects, knowledge is inadequate. Our aim has been to deepen understanding about women´s use of anabolic androgenic steroids. This phenomenological study is based on the reflective lifeworld research (RLR) approach. Lifeworld interviews were conducted with twelve women, aged 21-56 years, about their experiences of using anabolic steroids. The results show that women experience a sense of pride when they successfully achieve their goals. This is the driving force, triggering tension between suffering and success. Our research adds important knowledge from a reflective lifeworld perspective and shows that women´s use of anabolic androgenic steroids is a complex phenomenon. Understanding and knowledge are important in order to be able to meet and support women in their fears and difficulties.